The Role of Health Promotion on Smoke Free Area Implementation at Regional Work Unit Langsa City - Maswita; Etti Sudaryati; Juanita (Britain International for Academic Research (BIAR) Publisher, 2020)
Smoke free area implementation is one of the effective efforts to protect people from cigarette smoke. Health promotion can improve community behavior until they want and able to do healthy behavior and free from health problems. This study aims to explore the role of health promotion that has been implemented by the Langsa City Health Office in relation of smoke free area implementation, especially in regional work unit (SKPK). This is a qualitative study with narrative research design. Data are collected by indepth interview. The results show the role of the health promotion has been done in the implementation of the smoke free area are controlling social or environmental changes in the workplace through advocacy, socialization, development of promotional media, and monitoring and evaluation of smoke freea area implementation. The conclusion of this study that health promotion plays an important role in implementing the smoke free area including advocacy with regional government, disseminate information about the hazard of cigarettes to the public, set a regional regulation and socializing Qanun regarding smoke free area, and carried out smoke free area evaluation meeting to the head of regional work unit for commitment and support the smoke free area implementation at workplace.